Analisis Media Monitoring Pasca Dua Minggu Perilisan Chery Omoda E5 pada Bulan Februari – Maret 2024 - Abrar, Muhammad Fatih; Priyatna, Centurion Chandratama (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of the automotive industry in Indonesia has seen significant progress, especially in the increasing adoption of electric cars. As a large automotive market, Indonesia is shifting its focus towards environmentally friendly mobility, with growing interest in electric vehicles. Support from several state-owned companies marks an important step in promoting the use of electric cars in the country. One automotive brand interested in entering the competition in the electric car market in Indonesia is Chery. Chery, with its Chery Omoda E5 product, which is one of the popular car brands currently, offers various features at a more affordable price compared to its competitors. Netnography, as a qualitative descriptive research, aims to understand the phenomena experienced by research subjects such as behavior, perception, motivation, and actions holistically through descriptions in the form of words and language, in a specific natural context with various natural methods. Brand24, the tool used in this research, includes news and websites.